2018
DOI: 10.1002/mbo3.607
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibilities of Candidatus Liberibacter asiaticus‐infected and noninfected Diaphorina citri to entomopathogenic fungi and their detoxification enzyme activities under different temperatures

Abstract: Some entomopathogenic fungi species, Isaria fumosorosea, and Hirsutella citriformis were found to be efficient against the Asian citrus psyllid, Diaphorina citri Kuwayama (Hemiptera: Liviidae). However, the susceptibility to these fungi increases when the psyllid infected with Candidatus Liberibacter asiaticus (Las), which is transmitted by D. citri and causes citrus greening disease. In this study, we examined the Las-infected and Las-uninfected D. citri susceptibility to entomopathogenic fungi at different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…For example, the reduction of gene expression of general oxidases and esterases in Las-positive D. citri promote the susceptibility to most of the commercial insecticides (Tiwari et al 2011a, b, c). The decrease of these enzymes also causes susceptibility to entomopathogenic fungi (Hussain et al 2018). Moreover, Las-infected plants attract the parasitoid T. radiata, in addition to D. citri (Liu et al 2019).…”
Section: Interaction-based Hlb Managementmentioning
confidence: 99%
“…For example, the reduction of gene expression of general oxidases and esterases in Las-positive D. citri promote the susceptibility to most of the commercial insecticides (Tiwari et al 2011a, b, c). The decrease of these enzymes also causes susceptibility to entomopathogenic fungi (Hussain et al 2018). Moreover, Las-infected plants attract the parasitoid T. radiata, in addition to D. citri (Liu et al 2019).…”
Section: Interaction-based Hlb Managementmentioning
confidence: 99%
“…The Asian citrus psyllid (ACP), Diaphorina citri Kuwayama (Hemiptera: Psyllidae), is an economically important insect pest of citrus that disperses throughout the citrus growing regions, including tropical and subtropical Asia, Middle East, Central America, South America, Mexico, and Brazil (Grafton-Cardwell et al 2006;Hall et al 2012). Primarily, it attacks young flushes of citrus and can also attack the stressed citrus trees, if the population is high (Hussain et al 2018). Both nymphs and adult psyllid feed directly on phloem of tissues causing the distorted growth of plants as well as shoot dieback.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies on C Las infected D. citri have shown up‐regulated immune function, with induction of iron‐related proteins, cathepsins and haemocyanin (Kruse et al., 2018). Moreover, several studies have demonstrated that C Las promotes a reduction of gene expression of general oxidases and esterases in C Las‐positive D.citri , and the decrease of these genes causes susceptibility to most of the commercial insecticides and entomopathogenic fungi (Hussain et al., 2018; Tiwari et al., 2011). As such, while boosted fecundity may lead one to posit that the D. citri ‐ C Las relationship is a mutualism, further study on net fitness effects, accounting for other life‐history attributes, are clearly required.…”
Section: Discussionmentioning
confidence: 99%